Association between participation in a brief diabetes education programme and glycaemic control in adults with newly diagnosed diabetes. Issue 12 (26th June 2014) - Weaver, R. G.; Hemmelgarn, B. R.; Rabi, D. M.; Sargious, P. M.; Edwards, A. L.; Manns, B. J.; Tonelli, M.; James, M. T.
Abstract Aims To determine the association between participation in a brief introductory didactic diabetes education programme and change in HbA1c among individuals with newly diagnosed diabetes. Methods We identified a population‐based cohort of adults newly diagnosed with diabetes between October 2005 and June 2008 in Calgary, Canada, and conducted a retrospective cohort study by linking administrative and laboratory data with programme attendance data. We matched individuals who attended the programme within the first 6 months after diagnosis with those who did not attend, based on their propensity scores. We measured the change in HbA1c between time of diagnosis and 6–18 months later to determine the association between programme participation and change in HbA1c. Results HbA1c was measured at baseline and follow‐up for 7793 individuals, including 803 programme participants. After propensity score matching, programme participation was associated with a significantly greater adjusted mean reduction in HbA1c between baseline and follow‐up of 3.3 mmol/mol (95% CI 2.2–4.3) or 0.30% (95% CI 0.20–0.39). There was a significant interaction between baseline HbA1c and programme participation—the difference in adjusted mean reduction in HbA1c associated with programme participation ranged from 2.7 mmol/mol (0.25%) at baseline HbA1c of 53 mmol/mol (7%) to 6.2 mmol/mol (0.56%) at baseline HbA1c of 97 mmol/mol (11%). Conclusion Despite its brevity, participation in a diabetes education programme was associated with an additional reduction in HbA1c in newly diagnosed people that was comparable with that reported in trials of programmes targeted at those with prevalent diabetes.